2006
DOI: 10.1254/jphs.fp0060128
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of TRPM2 in Neuronal Cell Death by Hydrogen Peroxide

Abstract: -dependent neuronal death in a similar concentration range. Molecular cloning of TRPM2 cDNA from rat brain revealed several differences in amino acid sequences within the Nudix box region as compared with those of human and mouse TRPM2. ADPR-induced current responses, H 2 O 2 -induced Ca 2+ influx, and H 2 O 2 -induced cell death were induced in human embryonic kidney cells heterologously expressing rat TRPM2. Treatment of cultured neurons with small interfering RNA against rat TRPM2, which efficiently suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
152
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(160 citation statements)
references
References 35 publications
(40 reference statements)
6
152
0
1
Order By: Relevance
“…TRPM2 knock-out mice are protected against this infiltration and show reduced inflammation in a mouse model of colitis ulcerosa [131]. Neurons also express TRPM2 where it may be involved in H 2 O 2 -induced neuronal death [132,133].…”
Section: Redox Activation Of Trp Channels In Cell Deathmentioning
confidence: 99%
“…TRPM2 knock-out mice are protected against this infiltration and show reduced inflammation in a mouse model of colitis ulcerosa [131]. Neurons also express TRPM2 where it may be involved in H 2 O 2 -induced neuronal death [132,133].…”
Section: Redox Activation Of Trp Channels In Cell Deathmentioning
confidence: 99%
“…H 2 O 2 and cADPR have been proposed to potentiate the effects of ADPR at lower concentrations and to gate the TRPM2 channel directly at higher concentrations 15 . It has been suggested that H 2 O 2 -activated Ca 2+ influx through TRPM2 mediates pathophysiological cell death 14,17 . However, with regard to normal physiological cellular responses, the importance of H 2 O 2 -activated Ca 2+ influx remains to be elucidated.…”
mentioning
confidence: 99%
“…We have now extended this genotyping analysis to TRPM2. TRPM2 channels are highly abundant in immune cells, in insulin-secreting cells, and in the brain, where they are found in microglia and neuronal cells (8)(9)(10)(11). TRPM2 belongs to the transient receptor potential (TRP) superfamily, a group of cation channels that are expressed in virtually all tissue and cell types and are involved in various cellular functions, in the most part related to Ca 2ϩ signaling.…”
mentioning
confidence: 99%
“…TRPM2 has been implicated in cell death induced by oxidants (11,16). The presence of low Mg 2ϩ and high transition metals in the Western Pacific ALS and PD foci create conditions of increased oxidative stress (6).…”
mentioning
confidence: 99%